Preserving Natural Teeth VS Implant Replacement: A Scenario Based Survey - Alamri, Hadi M (Journal of Liaquat University of Medical & Health Sciences, 2020)
OBJECTIVE: To assess the preference of general dentists and dentists from various specialties regarding preservation of natural teeth vs. replacing it with an implant. METHODOLOGY: A survey in the form of an electronic scenario-based questionnaire was designed and the link was distributed among dentists from different specialties in Saudi Arabia over the duration of two months from the 28 th July to 28 th September, 2019. Following the demographic questions, participants were provided results of diagnostic aids for five clinical cases representing varying challenges, and participants were asked to either preserve the tooth or replace it with a dental implant. RESULTS: Total 203 participants completed the survey, 25% preferred implants over preserving the tooth in the first case, while 52% had the same preference in the second case, and 68% preferred extraction in the third case. The choice of extraction for cases 4 and 5 was 17% and 6% respectively. CONCLUSION: Many teeth are being extracted which could have been conserved. Ethically, the patient’s benefit and interest should be considered first while presenting various treatment options.